The Role of Muhammad Al-Fatih in Building Turkish Civilization - Nalurita, Do'ana Adinda; Muchtar, Nicky Estu Putu; Abu Bakar, Muhammad (Dirasah International Journal of Islamic Studies, 2024)
The Ottoman Turks were a nomadic tribe, often referred to as a nomadic nation. The Ottoman Turkish dynasty originated from the Qoyigh Oghus tribe, which inhabited the regions of Mongolia and northern China for approximately three centuries. They then migrated to Turkistan, Persia, and Iraq. They embraced Islam in the 9th or 10th centuries while they were settled in Central Asia. This research aims to explore the history of the Ottoman Turkish civilization founded by Sultan Muhammad Al-Fatih. They helped Sultan Alaudin II defeat Byzantium and were rewarded with the region of Asia Minor. Since then, they started developing their new territory. After Ertoghul died, leadership was continued by his sons Uthman, Orkhan, Murad I, Beyazid, Mehmed I, Murad II, and Mehmed II, among others. The idea of conquering Constantinople began to take shape during Orkhan's era and was realized during the time of Mehmed II (Muhammad Al-Fatih). The conquest of Constantinople was motivated by the Ottoman Turks' desire to control international trade activities in the area, destroy the dominance of Byzantium, the Eastern Roman Empire, and the Middle East region, and emphasize the strength of Islam's influence in the international world.